SOEDIRMAN-OERIP: DWITUNGGAL PIMPINAN TENTARA NASIONAL INDONESIA TAHUN 1945-1948 - Lucky Rohadi Nurohman; Ismi Novianti (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study aims to examine the concept of Dwitunggal which in terminology is defined as a very close and strong pair between two figures, in this case, Soedirman and Oerip Soemohardjo as the first supreme leaders of the Indonesian National Armed Forces in 1945-1948. The research method used in this research is library research. Data and information collection is carried out through books, scientific journals, and other research results that are worthy of being used as sources for research and have been critically and in-depth analyzed so that they can be used to support ideas in research. The findings obtained in this study are that differences in background are not always a barrier in building good relationships to achieve a goal, as seen in the story of Dwitunggal Soedirman-Oerip. It is known that Soedirman and Oerip had different backgrounds, namely Soedirman came from PETA while Oerip came from the KNIL, which at that time was considered a Dutch colonial army. Even so, the two can still work together and complement each other. Soedirman handled military politics while Oerip handled military techniques. This shows that Soedirman and Oerip did not see differences in one another's backgrounds as a barrier, but instead as a strength in building good relations to achieve common goals.